Propuesta de reingeniería de procesos para la empresa VALLTO agroindustrias cía. LTDA. de la ciudad de Loja - González Jaramillo, Milton Patricio (2016)
Today's society, demand from the corporate sector, qualified enterprises, highly productive, competitive technologically and administratively solvents. Taking as its premise the assertion mentioned in the preceding paragraph is to begin the preparation of this thesis, which originally had general objective was given: Make the proposal process reengineering model for the company Agro Co. Vallto. Ltda., In the city of Loja. The methodology used as a base element for information gathering and structuring same research was based on the use of the following methods: Historical Method, Analytical Method, Inductive Method Deductive Method; Likewise, it was necessary to resort to the application of the following techniques: observation, survey and interview; it should be emphasized in this chapter that the survey technique was applied to the 32 employees of the Company Agro Industries Co. Vallto. Ltda., And its 15 sub-distributors, and interview technique was applied successfully to the manager of the organization. This research work was designed taking into account the main processes that are being implemented in the company in this investigation, ie the operational processes making panela, whose proposed increasing 03H15 noted in its execution and the inclusion of 4 phases of paramount importance to the value chain of the process. Another reengineered business processes, was the purchase or acquisition of raw materials and inputs, whose proposal can be evidenced reducing its running time in 0400. Regarding the operating process payments to suppliers, a decrease in execution time of 0100 and reduction 2-step or links to their value chain was determined. As operational process cancellation wages and salaries, the proposal provides for the reduction reengineering of 0300 in its development and decreasing a link to its current value chain. Likewise, the proposal redesigned for the recruitment process, saves a total of 06H30 in its development. In conclusion, the proposed process reengineering designed to Vallto Agroindustry’s Cía. Ltda. Save a total of 11H15 in the execution of all processes. The main conclusions obtained through the preparation of this thesis were as follows: 1. The Company Agro Industries Co. Vallto. Ltda. Producer and marketer of panela block "La Palmira" enjoys broad public support and its flagship product is consumed by a large segment of the population of the southern region. 2. All processes currently taking place in the Agricultural Industry Co. Vallto Company. Ltda. Are the result of improvisation and empirical practices that do not obey technically elaborate design. The main recommendations suggested by the realization of this thesis were as follows: 1. In order to maintain and increase broad public support with which it currently Agribusiness Co. Vallto Company Ltd., its managers should undertake in the use of technological and administrative, able to allow the company to expand its share in the market tools, and therefore their customer base. 2. Agribusiness Co. Vallto managers. Ltda. With the implementation within the company every reengineering model proposed in this research work will be in full capacity to dispose of the company improvisation and the use of outdated and empirical operating practices